Impact of Gamified Micro-Learning on Attention Span and Academic Performance in Undergraduate Education - Fathima Raneesha (CV. Uruboros Publishing Group, 2025)
The growing use of digital technology in higher education has opened new possibilities for reshaping traditional teaching methods. One innovative strategy gaining attention is gamified micro-learning, which blends brief, well-structured learning units with game-like features such as points, badges, and instant feedback. This study explores how gamified micro-learning influences undergraduate students’ attention span and academic performance. A structured questionnaire was distributed to 80 students, and the data were analyzed using descriptive statistics. The results revealed that students reported a high average score for attention span (4.2) and a positive average score for academic performance (4.0). Attention levels showed consistent improvement throughout the learning sessions, rising from 3.5 to 4.3. Similarly, academic performance scores steadily increased from 3.8 to 4.1. These findings suggest that structured and interactive micro-learning experiences can strengthen focus and support academic growth. Overall, the study highlights the value of incorporating gamified approaches in higher education to boost engagement and encourage lasting learning outcomes.to academic improvement. The study supports the integration of gamified strategies in higher education to promote engagement and sustained learning outcomes.